Clinical Reasoning: A 23-Year-Old Woman Presenting With Cognitive Impairment and Gait Disturbance. (29th November 2022) - Chaity, Dimitra Khalil; Fearon, Conor; Alexander, Michael; Walsh, John; Austin, Neil; O'Byrne, James; Pastores, Gregory; Merwick, Aine; Saif, Muhammad; O'Dowd, Sean
Abstract : Metachromatic leukodystrophy (MLD) is a rare inherited lysosomal disorder. The condition progresses relentlessly, with severe disability typically established within 6–14 years of symptom onset. There is no cure, and limited treatment options are available to slow disease progression. We describe the case of a 23-year-old woman with forgetfulness, unsteady gait, and falls. Neurologic examination revealed intermittent dystonic posturing of the right upper and lower limb when walking. The Addenbrooke's Cognitive Examination (ACE) score was 70/100. MRI sequences demonstrated frontal-predominant atrophy and extensive white matter hyperintensity. Differential diagnoses such as autoimmune, inflammatory, and neoplastic diseases were excluded, and a genetic diagnosis was considered. Lysosomal enzyme testing showed low arylsulfatase with elevated urinary sulfatides, and genetic testing revealed a homozygous pathogenic mutation in the ARSA gene securing a diagnosis of adult-onset MLD. A male sibling also had early cognitive impairment and was found to have the same mutation. Hematopoietic stem cell transplantation (HSCT) was offered after discussion with experts. The male sibling died of multiple complications after HSCT. The index patient is now 24 months after HSCT, and disease progression has halted. This case highlights the challenges in the accurate diagnosis of adult-onset leukoencephalopathies and explores potential treatment strategies. A stepwise approach to the differential diagnosis of white matter diseases is demonstrated. HSCT may be an effective treatment, but the significant complication rate needs to be carefully considered.